2020
DOI: 10.1029/2019jg005213
|View full text |Cite
|
Sign up to set email alerts
|

Sediment Properties Drive Spatial Variability of Potential Methane Production and Oxidation in Small Streams

Abstract: Emissions of the potent greenhouse gas methane (CH 4 ) from streams and rivers are a significant component of global freshwater methane emissions. The distribution of CH 4 production and oxidation within stream sections and in vertical sediment profiles is not well understood, and the environmental controls on CH 4 production and emission in such systems create a significant challenge for assessing larger-scale dynamics. Here we investigate factors driving the spatial variability of sediment potential methane … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 83 publications
4
23
1
Order By: Relevance
“…The valley and channel gradient of the WS55 subcatchment may be responsible for stream CH 4 undersaturation: with lower organic matter and fewer sources of CH 4 , water flowing over steep gradients remains well oxygenated allowing CH 4 oxidation to use what little CH 4 is available. In reaches of small streams with high spatial variability in CH 4 production and oxidation, sediment nitrogen content was positively correlated with CH 4 production and oxidation (Bodmer et al., 2020). Because stream nitrogen concentrations vary among subwatersheds at Coweeta and over time, with forested streams typically having low stream nitrogen (Knoepp & Swank, 1997; Webster et al., 2016), future work characterizing differences in sediment nutrient contents may provide valuable insights into drivers of CH 4 from our study streams.…”
Section: Discussionmentioning
confidence: 99%
“…The valley and channel gradient of the WS55 subcatchment may be responsible for stream CH 4 undersaturation: with lower organic matter and fewer sources of CH 4 , water flowing over steep gradients remains well oxygenated allowing CH 4 oxidation to use what little CH 4 is available. In reaches of small streams with high spatial variability in CH 4 production and oxidation, sediment nitrogen content was positively correlated with CH 4 production and oxidation (Bodmer et al., 2020). Because stream nitrogen concentrations vary among subwatersheds at Coweeta and over time, with forested streams typically having low stream nitrogen (Knoepp & Swank, 1997; Webster et al., 2016), future work characterizing differences in sediment nutrient contents may provide valuable insights into drivers of CH 4 from our study streams.…”
Section: Discussionmentioning
confidence: 99%
“…2c). This variability may be caused by sediment properties that promote CH 4 production at microsites within the sediment (Bodmer et al 2020) or from preferential paths for bubble movement out of the sediment (Delsontro et al 2015), which we did not measure. Relatedly, some studies have found preferential sites for ebullition near aquatic edges (Bastviken et al 2008;Holgerson and Raymond 2016).…”
Section: Variability Of Ebullition At Multiple Spatial Scalesmentioning
confidence: 96%
“…Data on potential CH 4 oxidation (PMO) in freshwater ecosystems are also scarce (e.g. Oswald et al., 2015), but it was shown that PMO from river sediments increased with decreasing gravel size (Bodmer et al., 2020). Additional drivers of such distributions and rates in stream sediments have not been identified so far.…”
Section: Introductionmentioning
confidence: 99%